Macrophagic Stabilin-1 Restored Disruption of Vascular Integrity Caused by Sepsis - Lee, Wonhwa; Park, Seung-Yoon; Yoo, Youngbum; Kim, Soon-Young; Kim, Jung-Eun; Kim, Shin-Woo; Seo, Young-Kyo; Park, Eui Kyun; Kim, In-San; Bae, Jong-Sup (GEORG THIEME VERLAG KG, 2018)
Sepsis develops because of overwhelming inflammatory responses to bacterial infection, and disrupts vascular integrity. Stabilin-1 (STAB-1) is a phagocytic receptor, which mediates efferocytosis in a phosphatidylserine (PS)-dependent manner. STAB-1 is expected to play important roles in efferocytosis during sepsis. Here, we determined the role of STAB-1 in maintaining and restoring vascular integrity. Macrophages and vascular endothelial cells were used to assess the effect of STAB-1 on survival rate, phagocytic activity, vascular permeability and transendothelial migration (TEM). Additionally, we investigated whether the high-mobility group box 1 (HMGB1)-receptor for advanced glycated end products complex interfered with the binding of Stab1 to PS. Mortality rate was higher in the Stab1-knockout mice than in the wild-type mice, and STAB-1 deficiency was related to reduced macrophage-mediated efferocytosis and the disruption of vascular integrity, which increased vascular permeability, and enhanced TEM. STAB-1 deficiency promoted lung injury, and elevated the expression of sepsis markers. The exogenous application of the anti-HMGB1 neutralizing antibody improved efferocytosis, vascular integrity and survival rate in sepsis. Collectively, our findings indicated that STAB-1 regulated and maintained vascular integrity through the clearance of infected apoptotic endothelial cells. Moreover, our results suggested that interventions targeting vascular integrity by STAB-1 signalling are promising therapeutic approaches to sepsis.
Keywords: ACUTE LUNG INJURY; APOPTOTIC CELLS; ENDOTHELIAL-CELLS; SEPTIC SHOCK; PERITONEAL-MACROPHAGES; SCAVENGER RECEPTOR; ORGAN FAILURE; HOST-DEFENSE; PROTEIN-C; IN-VITRO